Design and analysis of a novel cable-actuated palletizing robot. (23rd November 2017) - Zi, Bin; Wang, Bingyao; Wang, Daoming
To meet the requirements in terms of large workspace, low inertia, and high degree of accuracy, a novel palletizing robot is introduced in this article. Utilizing spatial hybrid cable-actuated serial–parallel structure and parallelogram mechanism, the robot is able to achieve favorable potentials for stiffness, modularity, and reconfigurability. The kinematics and statics of the robot are investigated, and an algorithm is subsequently proposed to calculate the workspace of the limited degree of freedom cable-actuated serial–parallel manipulator. Then the workspace of the robot under different loads is calculated, and the topological properties of the workspace under different loads are compared and analyzed in detail. The results demonstrate that the proposed structure significantly enlarges the workspace and can also complete palletizing tasks effectively.